Characteristics of Biodegradable Foam with Proportional Treatment of Tapioca Flour and Soybean Peel Flour with Added Glycerol: Characteristics of Biodegradable Foam with Proportional Treatment of Tapioca Flour and Soybean Peel Flour with Added Glycerol - Fauzi, Arini Rista; Sarofa, Ulya; Rosida, Dedin F (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2024)
The food industry has increased so the need for food packaging has also increased. One of the packaging that is often used is Styrofoam, where Styrofoam contains chemical substances namely styrene, butyl hydroxytoluene, and polytyrene which can migrate to food and is harmful to humans because it is carcinogenic. One of the alternatives to styrofoam is bio-foam. Biofoam is an alternative packaging to replace styrofoam because it is made from natural raw materials, namely a mixture of starch, fibers, and synthetic polymers that are easily biodegradable. The natural ingredients used in the study were tapioca flour as a source of starch and yellow soybean hull flour as a source of fiber. The purpose of this study was to determine the effect of the ratio of proportions in opioids and yellow soybean hulls with the addition of glycerol on the characteristics of the bio-foam produced. This study uses a completely random design method with 2 factors. Factor I is the ratio of tapioca flour and yellow soybean hull flour, which is 70:30, 50:50, and 30:70. Factor II is the addition of glycerol by 5%, 10%, and 15%. The observation data was analyzed using ANOVA, if there was a real interaction or influence on the two treatments, then a DMRT test was carried out with a confidence level of 5%. The best treatment results were obtained through the Zeleny method, namely the treatment of the proportion of tapioca flour as a basic ingredient: yellow soybean hulls flour (30:70) and the addition of glycerol of 15% with the results of the analysis of moisture content of 15.76%, starch content of 17.53%, density of 1.13 gr/cm3, water absorption of 14.67%, biodegradability of 8.14% (±8 weeks) and tensile strength of 11.03Mpa